Analisis Hukum Penolakan Aksesi Framework Convention On Tobacco Control (FCTC) Terhadap Industri Hasil Tembakau di Indonesia - Cahya Wijaya; Ningrum Natasya Sirait; Mahmul Siregar; Sutiarnoto Sutiarnoto (Universitas Sumatera Utara, 2019)
Abstract. The tobacco industry becomes a controversial industry. In one side, it have very big role for the national economy, in other hand it has a negative impact on health and environment. To carry out tobacco control efforts WHO issued FCTC. Although Indonesia is one of the members (drafting committee) in initiating FCTC. However, Indonesia is the only country in the Asia Pacific region that did not signed the FCTC agreement. Therefore, the problem arises, namely how the international movement anti-tobacco campaign was carried out by the FCTC initiator, how is the rejection on the FCTC's accession by Indonesia government, how is the harmonization between legislation regarding tobacco control with the provisions of the FCTC although Indonesia not ratify the FCTC. Based on the results of the study it can be concluded that the anti-tobacco campaign movement was initiated by the FCA, the Bloomberg Initiative, non-governmental organizations and civil society. The international regime approach is used to replace the nicotine consumption pattern with NRT. Rejection of FCTC accession by the Indonesian government due to an interests. One of the interests are interests of state revenue. Although Indonesia did not ratify the FCTC, the Indonesian government adopted and harmonized laws and regulations with the provisions of the FCTC through various regulations including the regulation of advertising, promotion and sponsorship through Law Number 32 of 2002 concerning Broadcasting, Labeling and packaging through minister of health regulation Number 56 of 2017 concerning the pictorial health warning. In addition, the government has formulated a tobacco control roadmap. Keywords: accession, tobacco, industry, FCTC